The effect of high organizational commitment on increasing employee performance - Oktafien, Shinta; Santoso, Anton Budi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
This study aimed to examine the influence of organizational commitment on enhancing employee performance at PT. XXX. The population and sample comprised 52 employees of the company. Since the sample size matched the total population, a census (or saturated) sampling method was employed, in which all population members become part of the sample. This research is categorized as causal associative, seeking to identify the relationship between variables. The data processing and analysis involved descriptive statistics, research instrument testing (validity, reliability, and classical assumption tests), multiple regression analysis, and hypothesis testing (t-tests and F-tests), all conducted using SPSS version 23.0. The findings indicate that organizational commitment significantly affects employee performance at PT. XXX. In other words, the more committed individuals are to the organization, the greater their contributions toward boosting overall performance.